In the Study of the Witch: Women, Shadows, and the Academic Study of Religions - Zwissler, Laurel (Religions, 2018)
This article examines historically competing categories of magic and religion and their gendered traces in the history of religious studies. On one hand, we have a genealogy that traces the term, magic, back to an early modern European Christianity trying to understand itself through contrast with an imagined heresy that comes to be personified with a woman's face. On the other, we have contemporary political and religious communities that use the identification as Witches to reverse this version of dichotomous Christian gaze and legitimize religious difference, which also comes to be symbolized by a female body. Between these historical moments we have the beginning of the academic study of religion, the theoretical turn in which Christian-dominant scholarship comes to see itself on a continuum with, rather than opposed to, different religions, as first characterized by cultural evolution theories about the origins of religion. Especially given the field's theological roots, examining the constructed relationships between religion and magic, both of which represent crucial foci for early theorists, through the analytical lens of gender, which does not, provides opportunities to surface implicit assumptions of the current field about what is and is not worth studying.